Mothers’ perception of stress involved in parenting a diabetic child - Nwaokoro, Joakin Chidozie; Dozie, Simplicious IN; Amadi, Nkwa A; Emerole, Chima O; Ibe, Sally NO; Trapani, Josef; Nwaokoro, Ann Amaka (Asian Journal of Medical Sciences, 2014)
Objective: This study investigated mother’s perception of stress involved in parenting a diabetic child. Methods: Guided by a descriptive study, a target population which consisted of Maltese mothers with children having insulin-dependent diabetes that attended the outpatient diabetes clinic in St. Luke’s Hospital was surveyed. Well structured self-administered questionnaires were used in collecting data. Parental stress index (PSI) subscales vis-à-vis parental distress (PD), parent-child dysfunctional interaction (P-CDI) and diffi cult child (DC) were the yardsticks that were used to measure mother’s perception of stress involved in parenting a diabetic child. Generated data were subjected to descriptive statistics and correlation and regression analysis with regression line charts. Results: Results showed that mothers who had diabetic children were highly stressed with 19 out of 25 mothers scoring over 85th percentile in the parental stress index. It was also found that PSI subscales had the following trend in increasing order of stress on the mothers; P-CDI<DC<PD. This implied that PD had the greatest impact followed by DC and lastly P-CDI. Conclusion: It was therefore surmised that mothers with diabetic children perceive and experience a lot of stress as a result of having a diabetic child. Hence, it was recommended that further study should be carried out on father’s perception of stress involved in parenting a diabetic child. Asian Journal of Medical Science, Volume-5(3) 2014: 99-104 http://dx.doi.org/10.3126/ajms.v5i3.8910